(ISC)² SSCP systems security certified practitioner : official practice tests - Chapple, Mike; Seidl, David, CISSP (Sybex, a Wiley brand, 2019)
The (ISC)² SSCP Official Practice Tests is the only (ISC)²-endorsed set of practice questions for the Systems Security Certified Practitioner (SSCP). This book's first seven chapters cover each of the seven domains on the SSCP exam with sixty or more questions per domain, so you can focus your study efforts exactly where you need more review. When you feel well prepared, use the two complete practice exams from Sybex's online interactive learning environment as time trials to assess your readiness to take the exam.